Peran Guru Pendidikan Agama Islam dalam Membentuk Kepribadian Siswa - Sri Wegawati; Syarifah Salmah; Rabiatul Adawiah; Ahmad Risman; Nizari Rahman; M. Zulfa Alfiannur (JOEAI (Journal of Education and Instruction), 2026)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in shaping student personality at SMP Negeri 3 Kusan Hilir, Tanah Bumbu Regency; to identify the efforts made by these teachers in this process; and to determine the factors involved in shaping student personality at the school. The study employs a qualitative research design with a descriptive approach. The results indicate that the role of Islamic Religious Education teachers in shaping student personality at SMP Negeri 3 Kusan Hilir involves: a) analyzing the teacher's role in personality formation; b) analyzing the efforts undertaken by the teachers; and c) analyzing the factors involved in the process. The study concludes that the role of Islamic Religious Education teachers in shaping student personality at SMP Negeri 3 Kusan Hilir is crucial. Teachers do not merely act as instructors but are also capable of flexibly assuming various roles—serving as educators, parental figures, and friends to the students.   Keywords: Islamic Religious Education Teacher, Student Personality